2016
DOI: 10.2522/ptj.20150504
|View full text |Cite
|
Sign up to set email alerts
|

Synergic Effects of Rehabilitation and Intravenous Infusion of Mesenchymal Stem Cells After Stroke in Rats

Abstract: Background Intravenous infusion of mesenchymal stem cells (MSCs) derived from adult bone marrow improves behavioral function in rat stroke models. Rehabilitation therapy through physical exercise also provides therapeutic efficacy for cerebral ischemia. Objective The purpose of this study was to investigate whether synergic effects of daily rehabilitation and intravenous infusion of MSCs has therapeutic effects after stroke i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 38 publications
2
58
0
Order By: Relevance
“…35 Intravenous infusion of MSCs in the acute phase of stroke has been shown to have therapeutic efficacy in animal studies. 13,17,18,27,30 However, although there are pathophysiological differences between acute and chronic cerebral ischemia, only a limited number of studies have examined the therapeutic efficacy of MSCs during the chronic phase of stroke. Developing approaches to provide therapeutic efficacy in chronic ischemia represents an important area of investigation.…”
Section: Intravenous Infusion Of Mesenchymal Stem Cells Promotes Funcmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Intravenous infusion of MSCs in the acute phase of stroke has been shown to have therapeutic efficacy in animal studies. 13,17,18,27,30 However, although there are pathophysiological differences between acute and chronic cerebral ischemia, only a limited number of studies have examined the therapeutic efficacy of MSCs during the chronic phase of stroke. Developing approaches to provide therapeutic efficacy in chronic ischemia represents an important area of investigation.…”
Section: Intravenous Infusion Of Mesenchymal Stem Cells Promotes Funcmentioning
confidence: 99%
“…The MSC culture was prepared according to the methodology used in our previous studies. 16,17,27 Briefly, bone marrow was obtained from the femoral bones of adult rats (n = 16). The marrow was then diluted to 20 ml with Dulbecco's modified Eagle medium (DMEM; Sigma) and supplemented with 10% heat-inactivated fetal bovine serum (FBS; Thermo Fisher Scientific), 2 mM l-glutamine (Sigma), 100 U/ml penicillin, and 0.1 mg/ml streptomycin (Thermo Fisher Scientific) and incubated for 3 days (5% CO 2 , 37°C).…”
Section: Preparation Of Mscs From Rat Bone Marrowmentioning
confidence: 99%
“…In the present study, we showed that there is accumulation of intravenously administered MSCs in the injured region in CNS diseases, including stroke, which is consistent with previous studies. 4,16,30,34 It could be possible that infused MSCs migrated into the injured CNS tissue and provide beneficial effects. A hypothetical sequence of potential therapeutic mechanisms in a cell-based therapeutic approach for acute CNS insult is that beneficial effects may be provided from neuromodulators by MSC release, such as brain-derived neurotrophic factor 15,23 at early post-MSC infusion times (days).…”
Section: Discussionmentioning
confidence: 99%
“…The initial stroke volume evaluated with DWI was standardized at 220-370 mm 3 and excluded animals outside this range to assess the efficacy of MSCs following rtPA for a large ischemic injury. 30 We used a suture occlusion/reperfusion model in this study to investigate the effects of rtPA and MSCs following complete reperfusion. Physiological parameters (rectal temperature, blood pH, partial pressure of oxygen, partial pressure of carbon dioxide, and blood pressure) were maintained within normal ranges during surgery and transplantation procedures for all animals and did not significantly differ among the experimental groups.…”
Section: Cerebral Ischemic Modelmentioning
confidence: 99%
See 1 more Smart Citation